Implementation in Dominant Strategies under Complete and Incomplete Information - Repullo, Rafael (Review of Economic Studies, 1985)
This paper shows that if a social choice rule can be implemented in dominant strategies by an indirect mechanism, but there does not exist a direct mechanism that implements it in dominant strategies, then it must be the case that the original indirect mechanism does not implement the social choice rule in Nash strategies (under complete information) or in Bayesian strategies (under imcomplete information).